THE EFFECTIVENESS OF LITTLE THINKING MINDS PROGRAM IN DEVELOPING LANGUAGE SKILLS OF PRIMARY SCHOOL STUDENTS IN THE STATE OF JOHOR-MALAYSIA - Maysa Jehad Abdel Rahim Mohmadeya; Diaya Uddeen Deab Mahmoud Alzitawi; Muhammad Talhah Ajmain @ Jima’ain (Journal of Islamic, Social, Economics and Development, 2024)
This study is interested in observing the extent of the development of language skills using modern technologies through the use of the Little Thinking Minds program for primary school students in the state of Johor in Malaysia. The study also aims to measure the effectiveness of the Little Thinking Minds program in enhancing the language skills of primary school students. At the same time the study was prompted by the challenges that primary school students encounter in acquiring language and learning skills through modern. A quantitative approach was adopted in this study to obtain the best results, and the researcher concluded that the Little Thinking Minds Program will help students develop language skills by using all its tools designated for teaching non-native speakers.